2019
DOI: 10.1002/vms3.176
|View full text |Cite
|
Sign up to set email alerts
|

Detection of equid herpesviruses among different Arabian horse populations in Egypt

Abstract: Equid herpesviruses (EHVs) threaten equine health and can cause significant economic losses to the equine industry worldwide. Different equid herpesviruses, EHV‐1, EHV‐2, EHV‐4 and EHV5 are regularly detected among horse populations. In Egypt, monitoring is sporadic but EHV‐1 or EHV‐4 have been reported to circulate in the horse population. However, there is a lack of reports related to infection and health status of horses, likely due to the absence of regular diagnostic procedures. In the current study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
4
12
1
1
Order By: Relevance
“…Herein, the frequency of EHV-2 was detected in 33% which is lower than the percentage in Turkey 59% (41), Algeria 90% (42), and France 50% (28) whereas our data is comparable with those obtained by Azab et al (43) in Egypt as the percentage was 38%. However, these studies have been performed by examination of different sample types such as respiratory or genital tissues and this could explain the discrepancies with our data.…”
Section: Discussionsupporting
confidence: 84%
“…Herein, the frequency of EHV-2 was detected in 33% which is lower than the percentage in Turkey 59% (41), Algeria 90% (42), and France 50% (28) whereas our data is comparable with those obtained by Azab et al (43) in Egypt as the percentage was 38%. However, these studies have been performed by examination of different sample types such as respiratory or genital tissues and this could explain the discrepancies with our data.…”
Section: Discussionsupporting
confidence: 84%
“…Azab et al [28] reported that the variation in the prevalence of the disease among studies is attributed to geographical variability and environmental factors. However, at present, a possible explanation of why equids residing in different agroecology have varying susceptibility to EHV infection could not be given.…”
Section: Discussionmentioning
confidence: 99%
“…For diagnosis of EHV-4 infection, PCR has become the test of choice due to its high sensitivity and specificity. Nowadays, PCR has been routinely used as molecular diagnostic tool for equine herpes virus infections in various countries and many prevalence studies had been carried out using PCR as a single diagnostic tool (Ataseven et al, 2009;Mohamed et al, 2017;Negussie et al, 2017;Azab et al, 2019). The present study was carried out in small scale only to standardize a PCR test for diagnosis of EHV-4 infection at local level.…”
Section: Nucleic Acid Extraction and Pcr Amplificationmentioning
confidence: 99%